TGF-β1 is present at high levels in wound fluid from breast cancer patients immediately post-surgery, and is not increased by Intraoperative Radiation Therapy (IORT) - Scherer, Sandra; Schmaus, Anja; Neumaier, Christian; Herskind, Carsten; Veldwijk, Marlon Romano; Wenz, Frederik; Sleeman, Jonathan P. (PLOS ONE, 2016)
In patients with low-risk breast cancer, intraoperative radiotherapy (IORT) during breast-conserving surgery is a novel and convenient treatment option for delivering a single high dose of irradiation directly to the tumour bed. However, edema and fibrosis can develop after surgery and radiotherapy, which can subsequently impair quality of life. TGF- β is a strong inducer of the extracellular matrix component hyaluronan (HA). TGF-β expression and HA metabolism can be modulated by irradiation experimentally, and are involved in edema and fibrosis. We therefore hypothesized that IORT may regulate these factors.Wound fluid (WF) draining from breast lumpectomy sites was collected and levels of TGF-β1 and HA were determined by ELISA. Proliferation and marker expression was analyzed in primary lymphatic endothelial cells (LECs) treated with recombinant TGF-β or WF. Our results show that IORT does not change TGF-β1 or HA levels in wound fluid draining from breast lumpectomy sites, and does not lead to accumulation of sHA oligosaccharides. Nevertheless, concentrations of TGF-β1 were high in WF from patients regardless of IORT, at concentrations well above those associated with fibrosis and the suppression of LEC identity. Consistently, we found that TGF-β in WF is active and inhibits LEC proliferation. Furthermore, all three TGF-β isoforms inhibited LEC proliferation and suppressed LEC marker expression at pathophysiologically relevant concentrations. Given that TGF-β contributes to edema and plays a role in the regulation of LEC identity, we suggest that inhibition of TGF-β directly after surgery might prevent the development of side effects such as edema and fibrosis.